I'm having trouble calculating the Fourier Transform of the sin function. Specifically, the function

$ G(\omega)=\int _{-\infty}^{\infty} g(t)\ e^{-i \omega t} dt $

For the fourier transform of

$ g(t)=\sin (2 \pi A t)$

the answer is:

$ \dfrac{\pi}{i}[ \delta(\omega - 2 \pi A)-\delta(\omega + 2 \pi A)] $.

My only problem is that I don't understand why the factor in the front is $\pi/i $ , and not just the $ 1/(2i) $ that falls out of the expansion of the sine function.

  • 2
    $\begingroup$ ${\cal F} (t \mapsto e^{iat})(\omega) = 2 \pi \delta(\omega-a)$. $\endgroup$ – copper.hat Dec 3 '14 at 5:32
  • $\begingroup$ Hey copperhat, where does the 2*pi come from? When i do the FT, i just get the dirac delta.. $\endgroup$ – user63602 Dec 3 '14 at 5:38
  • 1
    $\begingroup$ ${\cal F}(\delta)(\omega) = 1$, then use the inverse transform (${\cal F} \hat{f} = 2 \pi f$) which gives ${\cal F} (t \mapsto 1) = 2 \pi \delta$. $\endgroup$ – copper.hat Dec 3 '14 at 6:41

The short answer is that the $2 \pi$ comes from the inversion formula.

Here is an informal perspective which gives as hint as to how this can be made more rigorous:

A distribution is defined by its action on a space of nicely behaved test functions.

For a function $f$ from a restricted class of ordinary functions, we can define a distribution $T_f$ by $T_f(\phi) = \int f \phi$. For the function $t \mapsto 1$, we get $T_1(\phi) = \int \phi$.

The '$\delta$ function' is defined by the distribution $T_\delta(\phi) = \phi(0)$. That is, it takes a test function $\phi$ and returns its value at $0$.

The Fourier transform of a distribution is defined by $\hat{T_f}(\phi) = T_f(\hat{\phi})$, where $\hat{\phi}$ is the ordinary Fourier transform of $\phi$.

We see that ${\hat{T}_1}(\phi) = T_1(\hat{\phi}) = \int \hat{\phi}$.

The standard inversion formula shows that $\int \hat{\phi} = 2 \pi \phi(0)$, which gives ${\hat{T}_1}(\phi) = 2 \pi T_\delta(\phi)$, or more succinctly, ${\hat{T}_1} = 2 \pi T_\delta$.

The same sort of analysis shows that ${\hat{T}_{t \mapsto e^{iat}}}(\phi) = 2 \pi \phi(a) = 2 \pi T_\delta(\omega \mapsto \phi(\omega+a))$. The last expression may be written informally as $T_{ \omega \mapsto 2 \pi \delta(\omega-a) } (\phi)$, which is the desired result.



$ \sin( 2 \pi A t) = (e^ { i\ 2 \pi A t} - e^ {- i\ 2 \pi A t} )/ ( 2 i) $


Use the concept of duality property

$$x(t) \rightleftharpoons X(\omega$$

$$X(t) \rightleftharpoons 2\pi x(-\omega)$$

$$\delta(t) \rightleftharpoons 1$$

$$ 1 \rightleftharpoons 2\pi \delta(-\omega)$$

Since $\delta(\omega)$ is a even function

$$ 1 \rightleftharpoons 2\pi \delta(\omega)$$

$$e^{j\omega_0t} \rightleftharpoons 2\pi \delta(\omega-\omega_0)$$

$$e^{-j\omega_0t} \rightleftharpoons 2\pi \delta(\omega+\omega_0)$$

$$sin(\omega_0t) \rightleftharpoons \frac{\pi}{j} [ \delta(\omega-\omega_0) - \delta(\omega+\omega_0)]$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.